COMPETENCY ALIGNMENT AND LECTURER JOB SATISFACTION IN VOCATIONAL HIGHER EDUCATION - Arina Luthfini Lubis; Siti Meisyaroh; Novi Hendri Adi; Rahmadi Rahmadi; John Friadi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
Competency alignment and job placement are important aspects of human resource management in vocational higher education because they influence lecturers’ job satisfaction. This study explores lecturers’ perspectives on competency alignment, job placement, and job satisfaction. A qualitative phenomenological approach was employed. Data were collected through in-depth interviews with ten lecturers who had experience in structural positions and analyzed using the Miles and Huberman model. The findings indicate that not all lecturers perceive their positions as aligned with their competencies. Job placement is generally carried out through direct assignments from institutional leaders and is often viewed as an additional workload because lecturers must continue fulfilling their teaching, research, and community service responsibilities. Changes in structural positions also create perceptions of reduced opportunities for contribution and career uncertainty. The study reveals that lecturers’ job satisfaction is influenced more by competency utilization, opportunities to contribute, and professional recognition than by the existence of a structural position itself. These findings highlight the importance of competency-based job placement and sustainable opportunities for lecturers to contribute to institutional development.